Cyberwar and information warfare - Ventre, Daniel (London : ISTE ; Hoboken, NJ : John Wiley, 2011)
Integrating empirical, conceptual, and theoretical approaches, this book presents the thinking of researchers and experts in the fields of cybersecurity, cyberdefense, and information warfare. The aim of this book is to analyze the processes of information warfare and cyberwarfare through the historical, operational and strategic perspectives of cyberattacks. Cyberwar and Information Warfare is of extreme use to experts in security studies and intelligence studies, defense universities, ministries of defense and security, and anyone studying political sciences, international relations, g.
5.3. Concept of critical infrastructure5.3.1. Generalized definition of the notion of critical infrastructure; 5.3.2. System interdependence; 5.4. Different phases of a cyberattack; 5.4.1. Intelligence phase; 5.4.2. Planning phase; 5.4.3. Conduct phase; 5.5. A few "elementary building blocks"; 5.5.1. General tactical framework; 5.5.2. Attacks on people; 5.5.3. Opinion manipulation and area control; 5.5.4. Military computer attack in a conventional operation; 5.6. Example scenario; 5.6.1. Tactical scenario; 5.6.2. The order of events; 5.6.3. Analysis; 5.7. Conclusion; 5.8. Bibliography.
Includes bibliographical references and index.
Print version record.
Keywords: Information warfare; Psychological warfare; Computer crimes; Computer crimes; Information warfare; Psychological warfare; HISTORY -- Military -- Biological & Chemical Warfare; Computer crimes; Information warfare; Psychological warfare; Electronic books